Prevalence of skin disease in a population-based sample of adults from five European countries - Svensson, Åke; Ofenloch, Robert; Diepgen, Thomas L. (British journal of dermatology, 2018)
Background There is a lack of prevalence data on skin diseases in the general adult population; most studies have been carried out in small, national or consecutive clinical samples. Objectives To determine the prevalence of common skin disease in the general European population and to assess differences in the characteristics of treatment between countries. Methods A random sample consisting of 12 377 participants aged 18-74 years was drawn from the general population of five European countries (Germany, Italy, the Netherlands, Portugal and Sweden). This was a cross-sectional study and all participants were interviewed using a standardized questionnaire that assessed the occurrence of 10 common skin diseases during lifetime, past year and past month. If a skin disease was reported, we additionally assessed who performed the diagnosis and treatment, and whether drugs had been prescribed. Results The most common skin disease was warts (41·3%), followed by acne (19·2%) and contact dermatitis (15·0%). In general, women were more often affected by skin diseases compared with men; only skin cancer had a slightly higher prevalence in men. The prevalence of skin diseases in northern countries (Germany, the Netherlands and Sweden) was generally higher than in the southern countries (Italy and Portugal). In the Netherlands the treatment of skin diseases was less often performed by a dermatologist compared with the other countries. Conclusions The prevalence estimates reported in this study are derived from a representative sample of the general population. Data assessment was performed comprehensively across countries, thus country-specific prevalence estimates are comparable.
First published: 16 December 2017
Gesehen am 20.06.2018